NTP42, a novel antagonist of the thromboxane receptor, attenuates experimentally induced pulmonary arterial hypertension - Eamon P. Mulvaney; Helen M. Reid; Lucia Bialesova; Annie Bouchard; Dany Salvail; B. Therese Kinsella (BMC Pulmonary Medicine, 2020)
Abstract Background NTP42 is a novel antagonist of the thromboxane prostanoid receptor (TP), currently in development for the treatment of pulmonary arterial hypertension (PAH). PAH is a devastating disease with multiple pathophysiological hallmarks including excessive pulmonary vasoconstriction, vascular remodelling, inflammation, fibrosis, in situ thrombosis and right ventricular hypertrophy. Signalling through the TP, thromboxane (TX) A2 is a potent vasoconstrictor and mediator of platelet aggregation. It is also a pro-mitogenic, pro-inflammatory and pro-fibrotic agent. Moreover, the TP also mediates the adverse actions of the isoprostane 8-iso-prostaglandin F2α, a free-radical-derived product of arachidonic acid produced in abundance during oxidative injury. Mechanistically, TP antagonists should treat most of the hallmarks of PAH, including inhibiting the excessive vasoconstriction and pulmonary artery remodelling, in situ thrombosis, inflammation and fibrosis. This study aimed to investigate the efficacy of NTP42 in the monocrotaline (MCT)-induced PAH rat model, alongside current standard-of-care drugs. Methods PAH was induced by subcutaneous injection of 60 mg/kg MCT in male Wistar–Kyoto rats. Animals were assigned into groups: 1. ‘No MCT’; 2. ‘MCT Only’; 3. MCT + NTP42 (0.25 mg/kg BID); 4. MCT + Sildenafil (50 mg/kg BID), and 5. MCT + Selexipag (1 mg/kg BID), where 28-day drug treatment was initiated within 24 h post-MCT. Results From haemodynamic assessments, NTP42 reduced the MCT-induced PAH, including mean pulmonary arterial pressure (mPAP) and right systolic ventricular pressure (RSVP), being at least comparable to the standard-of-care drugs Sildenafil or Selexipag in bringing about these effects. Moreover, NTP42 was superior to Sildenafil and Selexipag in significantly reducing pulmonary vascular remodelling, inflammatory mast cell infiltration and fibrosis in MCT-treated animals. Conclusions These findings suggest that NTP42 and antagonism of the TP signalling pathway have a relevant role in alleviating the pathophysiology of PAH, representing a novel therapeutic target with marked benefits over existing standard-of-care therapies.